Globalization for Sale - Michael Blanga-Gubbay; Paola Conconi; Mathieu Parenti (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the role of firms in the political economy of trade agreements. Using detailed information from lobbying reports filed under the Lobbying Disclosure Act, we find that virtually all firms that lobby on free trade agreements (FTAs) support their ratification. Moreover, relative to non-lobbying firms, lobbying firms are larger, and more likely to be engaged in international trade and to operate in comparative advantage sectors. To rationalize these findings, we develop a model in which heterogeneous firms decide whether to lobby and how much to spend in favor or against a proposed FTA. We show that the distributional effects are asymmetric: the winners from the FTA have higher stakes in the agreement than the losers, which explains why only pro-FTA firms select into lobbying. The model also delivers predictions on the intensive margin of lobbying. In line with these predictions, we find that firms spend more supporting agreements that generate larger potential gains - in terms of the extent of the reduction of tariffs on their final goods and intermediate inputs, the depth of the agreement, and the export and sourcing potential of the FTA partners - and when politicians are less likely to be in favor of ratification.
Keywords: F13; F53; F61; 330; trade agreements; endogeneous lobbying; heterogeneous firms